METHOD OF MUNASABAH IN KORAN AND THE VALUES OF EDUCATION ON IT - Dartim Dartim (Universitas Muhammadiyah Surakarta, 2021)
Beside as part as being a revelation, Koran is also a human guide book in carrying out all life activities. So understanding it is an obligation for every Muslim, one method for that is munasabah Koran. In addition to knowing the meaning in each verse or letter. The munasabah method is very important in building a framework of thought in the world of science and education. This paper with the content analysis method will try to explain how the munasabah in the Koran inspires the development of educational values.